2021
DOI: 10.3389/fphar.2021.730525
|View full text |Cite
|
Sign up to set email alerts
|

Danlou Tablet Activates Autophagy of Vascular Adventitial Fibroblasts Through PI3K/Akt/mTOR to Protect Cells From Damage Caused by Atherosclerosis

Abstract: Danlou tablet (DLT), a commercial Chinese patent medicine, has been widely used to treat cardiovascular diseases for many years. Atherosclerosis (AS) is the leading cause of cardiovascular disease. Increasing evidence indicates that autophagy plays a vital role in the development of AS. Here we investigated whether DLT could activate autophagy to improve AS and further clarified its underlying mechanisms. In an ApoE−/− mice model, the results of Oil red O, Masson’s trichrome, and H&E staining technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A previous study reported that the AKT/mTOR signaling pathway promoted the cellular activities of fibroblasts; notably, after intervening with LY294002 (an inhibitor of the AKT/mTOR signaling pathway), cellular viability and proliferation were reduced (3). Previous studies have also confirmed the inhibitory effect of AKT/mTOR signaling inactivation on fibroblast migration; notably, applying Morin (an anti-arthritis compound) has been shown to reduce the migration of fibroblasts in rheumatoid arthritis (56) and Danlou tablet (a Chinese medicine used to treat cardiovascular diseases) has been reported to restrain the migration of vascular adventitial fibroblasts in atherosclerosis (57). Furthermore, Lu et al revealed that an antibody against programmed cell death ligand 1 could inhibit fibroblast proliferation, migration and ECM deposition in pulmonary fibrosis through regulating the AKT/mTOR signaling pathway (58).…”
Section: Discussionmentioning
confidence: 87%
“…A previous study reported that the AKT/mTOR signaling pathway promoted the cellular activities of fibroblasts; notably, after intervening with LY294002 (an inhibitor of the AKT/mTOR signaling pathway), cellular viability and proliferation were reduced (3). Previous studies have also confirmed the inhibitory effect of AKT/mTOR signaling inactivation on fibroblast migration; notably, applying Morin (an anti-arthritis compound) has been shown to reduce the migration of fibroblasts in rheumatoid arthritis (56) and Danlou tablet (a Chinese medicine used to treat cardiovascular diseases) has been reported to restrain the migration of vascular adventitial fibroblasts in atherosclerosis (57). Furthermore, Lu et al revealed that an antibody against programmed cell death ligand 1 could inhibit fibroblast proliferation, migration and ECM deposition in pulmonary fibrosis through regulating the AKT/mTOR signaling pathway (58).…”
Section: Discussionmentioning
confidence: 87%
“…The result of Oil Red O-staining showed that the lesion area was decreased in the CAP group when compared with the HFD group ( p < 0.01) ( Figure 1 B). The collagen levels in the aortic sinus were correlated with the stability of atherosclerotic plaques [ 17 ], and therefore we further evaluated the collagen levels by Masson’s trichrome staining. The results showed that the levels of collagen in the aortic sinus were increased in the CAP group when compared with the HFD group ( p < 0.01) ( Figure 1 C), indicating that capsaicin administration was beneficial for the stability of atherosclerotic plaques.…”
Section: Resultsmentioning
confidence: 99%
“…DL comprises ten different types of botanical drugs such as Trichosanthes rosthornii Harms [Cucurbitaceae] and Allium macrostemon Bunge [Amaryllidaceae] with components primarily as artemisinolide (17.49%), β -Elemene (11.07%), and (-) Spartol (8.95%) ( Zhang et al, 2016 ). Studies of mechanism indicated that DL could inhibit NF-κB signaling, trigger PPARα/ABCA1 signaling pathway, and activate PI3K/Akt/mTOR-mediated autophagy of vascular adventitial fibroblasts, thus preventing atherosclerosis ( Hao et al, 2019 ; Wang L. et al, 2021 ). SXBX is composed of seven traditional Chinese medicines such as Panax ginseng C.A.Mey [Araliaceae], Cinnamomum verum J. Presl [Lauraceae], and Liquidambar orientalis Mill [Altingiaceae].…”
Section: Discussionmentioning
confidence: 99%